BUDAYA ORGANISASI, KEPUASAN KERJA DAN KARAKTERISTIK PENGARUHNYA TERHADAP KOMITMEN ORGANISASIONAL (pada Karyawan KOP “SAE” Pujon Malang Jawa Timur) - Ulya Munzilatul Qushwa; Hadi Sunaryo (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACT At present, an organization needs human resources. Therefore an organization always increases organizational commitment and various ways are carried out by the organization to find out the factors that cause a decrease or increase in organizational commitment. The purpose of this study is to analyze organizational culture, job satisfaction and individual characteristics of organizational commitment. The research object chosen in this study was the Pujon Malang